Heterotrophic growth of thraustochytrids strains: screening, optimization and scale-up - Santos, Mafalda Trovão dos (2022)
Thraustochytrids are well-reported microorganisms with an outstanding ability to produce and accumulate polyunsaturated fatty acids (PUFAs), particularly docosahexaenoic acid (DHA). In the present study, a lab-scale optimization on medium and fermentation parameters, was carried out with Aurantiochytrium sp. 0043 AA aiming at high cell biomass, lipids and DHA yields. Medium optimization was performed based on the literature, focused on the screening of different C and N sources, on the concentration of each source as well as on the ratio and feeding strategies. In addition, other fermentation parameters were optimized, such as initial inoculum conditions (volume, age and stage), different oxygen transfer rates and pH. Later on, the growth performances of Aurantiochytrium sp. 0050 AA and 0051 AA, were compared to strain 0043 AA. The respective cryopreservation processes weres completed and the banks validated, with the exception of the master cell bank (MCB1) of strain 0051 AA. Overall, lab-scale optimization of strain 0043 AA allowed to increase biomass yield by 2fold and improve lipid and DHA contents from 22.78% and 1.25% to 31.14% and 29.66%, respectively. Furthermore, with strain 0051 AA, a maximum dry weight (DW) of 80.15 g/L was obtained, with concomitant lipid and DHA contents of 60.34% and 38.81%, respectively. Although several conditions were tested in the 5 L bench-top reactor, cultivation was not successful due to the shear-sensitive cells of this species and further trials on fermentation parameters and reactor design are required to enable the scale-up.